Point-of-Care Ultrasound on Management of Cellulitis Versus Local Angioedema in the Pediatric Emergency Department. Issue 2 (23rd February 2022) - Tay, Ee Tein; Ngai, Ka Ming; Tsung, James W.; Sanders, Jennifer E.
Abstract : Supplemental digital content is available in the text. Abstract : Objectives: To evaluate whether ultrasound can differentiate between cellulitis and angioedema from insect bites in pediatric patients. Methods: A prospective, pre-post study in an urban pediatric emergency department of patients younger than 21 years with soft tissue swelling from insect bites without abscesses were enrolled. Treating physician's pretest opinions regarding the diagnosis and need for antibiotics were determined. Ultrasound of the affected areas was performed, and effects on management were recorded. Further imaging, medications, and disposition were at the discretion of the enrolling physician. Phone call follow-ups were made within a week of presentation. Results: Among 103 patients enrolled with soft tissue swelling secondary to insect bites, ultrasound changed the management in 27 (26%) patients (95% confidence interval [CI], 18–35%). Of the patients who were indeterminate or believed to require antibiotics, ultrasound changed management in 6 (23%) of 26 patients (95% CI, 6%–40%). In those patients who were believed not to require antibiotics, ultrasound changed management in 12 (16%) 77 patients (95% CI, 7%–24%). Patients with diagnosis of local angioedema achieved symptom resolution 1.4 days sooner than patients diagnosed with cellulitis (mean, −1.389; 95% CI, −2.087 to −0.690; P < 0.001). No patient who was initially diagnosed as local angioedema received antibiotics upon patient follow-up. Conclusions: Point-of-care ultrasound changed physician management in 1 of 4 patients in the pediatric emergency department with soft tissue swelling secondary to insect bites. Ultrasound may guide the management in these patients and lead to improved antibiotic stewardship in conjunction with history and physical examination.